Disponibilidade hídrica potencial em face da distribuição espaço-temporal das precipitações no Estado do Rio Grande do Norte - Gonçalves, Sérgio Carvalho (2009)
The state of Rio Grande do Norte, possessor of an extremely irregular regime of rains, has the necessity of enlarge and specify the researches about its own hydro-climatic conditions, to achieve trustworthy results that are able to minimize the adversities imposed by these conditions and make possible the implementation of a better planning in the economic activities and of subsistence that somehow utilize of the multiple uses of hydro resources of the State. This way, the daily values observed from the pluviometric series of 166 posts, with 45 years uninterrupted of historic data, were adjusted to the incomplete gamma function to the determination of the probability of rain in the 36 period of ten days in which the year was divided. To the attainment of the α and β parameters of this function it was applied the method of the maximum verisimilitude allowing, in the end, to analyze the temporal and spatial distribution of the rain in the level of 75% of probability. The values of potential evapo-transpiration were calculated by the Linacre method that, through the SURFER software, were confronted with the dependant rain, obtaining, in this way, the spatialization of the potential hydro availability, which the values can be known to any period of ten days of the year, city and/or region of the state of Rio Grande do Norte. With the identification of the main meteorological systems that act in the State, we sought to better comprehend how this systems interfere, in the irregular regime of rain, in the situations of several clime in the major part of Rio Grande do Norte and in the hydro regional balance. And, finally, with these data in hand and with the generated maps, we verified that space-temporal distribution of the rain and of the potential hydro availability were heterogeneous in the whole State, mainly in the West and Central regions, inserted in potiguar s semi-arid, which, after the period of the rains station, suffers with dry season and length drought during the rest of the year